FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI - TJHAI FUNG JIN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2002)
This study investigates the influence factors of AIS performance. user capability, top management support, organization size, formalization of IS development, existence of steering committe, program user training and education and location of IS department as influence factors and on AIS satisfactiction and user system usage as surrogate of AIS performance. Sixty-seven respondents from 140 manufacturer company listed in Jakarta Stock Exchange and have a representative office or headquarter at Jakarta, that questionnaire sent were involved in this study. The research questionnaire is to be completed by users of the AIS in those companies and assist in measuring user perception in relation to both influence factors and AIS performance. The questionnaires were spread to staff level on general accounting, finance, tax and cost accounting department. This study found that user will be satisfied with the information system used in their company if top management support increase, higher formalization in information system development, bigger company size, introduce the user training and education program, and department of IS locate under anaother department (dependent). On the another hand, higher system usage will be receipt when higher user involvement and steering committe exist